Parental Rejection and Child Emotion Dysregulation: The Mediating Role of Shame - Romano, Giulia; Piskorz-Ryń, Oriana; Camilo Ríos, Juan (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to examine the mediating role of shame in the relationship between parental rejection and child emotion dysregulation among adolescents in Colombia.Methods: The research employed a descriptive correlational design using a sample of 482 adolescents aged 10 to 17, selected based on the Morgan and Krejcie sampling table. Participants were recruited from public and private schools in urban areas of Colombia. Standardized tools were used to measure perceived parental rejection, internalized shame, and emotion dysregulation. Data were analyzed using Pearson correlation to assess bivariate relationships and Structural Equation Modeling (SEM) in AMOS-21 to evaluate the direct, indirect, and total effects within the hypothesized mediation model. Assumptions for normality, linearity, and multicollinearity were checked and confirmed prior to analysis.Findings: Pearson correlation analysis revealed significant positive associations between parental rejection and shame (r = .61, p < .001), parental rejection and emotion dysregulation (r = .58, p < .001), and shame and emotion dysregulation (r = .65, p < .001). SEM results indicated that the structural model had a good fit (χ²(84) = 211.63, χ²/df = 2.52, CFI = 0.96, TLI = 0.95, RMSEA = 0.055). Parental rejection significantly predicted shame (β = 0.61, p < .001), and shame significantly predicted emotion dysregulation (β = 0.54, p < .001). A significant direct effect was found from parental rejection to emotion dysregulation (β = 0.33, p < .001), alongside a significant indirect effect through shame (β = 0.33, p < .001), supporting full mediation.Conclusion: The findings suggest that shame is a critical emotional mechanism linking perceived parental rejection to difficulties in emotion regulation among adolescents. Targeting shame in therapeutic and educational interventions may mitigate the negative emotional consequences of parental rejection and promote emotional resilience in youth.